Effect Leadership and Organizational Commitment against Discipline and Motivation The Impact on Employee Performance Sukoharjo District Agricultural Office - Widyastuti, Dina (STIE AUB Surakarta)
The purpose of this study was to determine and analyze empirically the effect of leadership and discipline on organizational commitment and motivation that have an impact on employee performance Sukoharjo District Agricultural Office. The analysis technique used is using validity and reliability test, linearity test, regression analysis, path analysis, t test, F test, test the coefficient of determination and correlation analysis. The results showed that the t-test on the first equation can be concluded that leadership and discipline variable positive and significant impact on organizational commitment. T test on the second equation can be concluded that the variables of leadership and discipline and significant positive effect on the motivation. T test on the third equation can be concluded that the leadership, discipline, organizational commitment and motivation positive and significant impact on performance. Test results simultaneously (Test F) in the third equation can be concluded jointly independent variables affect the performance value of R2 can be interpreted totaling 0.938 variation, Employee Performance in the Department of Agriculture Sukoharjo explained by variables of leadership, discipline, organizational commitment, motivation and amounted to 93 , 8% and the remaining 6.2% described other variables outside the model as an example of job stress research, training and so on. Results showed that the direct effect of effective discipline through a direct path, while effective leadership through indirect pathways. Leadership through motivation is the most dominant variable affecting the performance of employees at the Department of Agriculture Sukoharjo.